Special relationships: Anglo-American affinities and antagonisms 1854-1936 - Beer, Janet (Manchester University Press, 2002)
This collection of essays by leading scholars of American literature and culture has emerged out of recent debates on the historical, geographical, symbolic, and cultural significance of the Atlantic, as well as new work in the area of Transatlantic Studies. In a series of fascinating essays the authors have produced diverse and innovative interventions in the field of Anglo-American literary relations. The authors discussed range from Gertrude Stein to Alfred North Whitehead, Charlotte Perkins Gilman to Sarah Grand, Henry James to George Eliot, Elizabeth Stoddard to Charlotte Bronte, Mark Twain to Walter Scott through to Djuna Barnes and Evelyn Waugh. Subjects discussed include Scottish-American literary relations, the Atlanticist dimension of Spiritualism, American interventions in the debate about Highland clearances, American slavery and British pastoralism.